Transection of Sternothyroid muscle increases the rate of exposure of the external branch of the superior laryngeal nerve during thyroidectomy - Reda Fawzy Abbas Ali; Ahmed Ibrahim Mousa Ebeed; Ahmed Mahmoud Ahmed Aouf; Mohammad Mahmoud Ahmed Aouf; Ali Gamal Ali El Ouny; Saad Eldesuoky Helmy Elzayat (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the benefits of transection of the sternothyroid muscle compared to conventional approach for detecting the external branch of the superior laryngeal nerve while dealing with the upper pole of the thyroid gland. Method: The randomised controlled clinical trial was conducted at Kafrelsheikh University Hospital, Egypt, from January 2021 to January 2022, and comprised patients who were eligible for total thyroidectomy and met the American Thyroid Association guidelines. They were randomised and divided into conventional approach group A and sternothyroid muscle transection approach group B. The rate of exposure of the external branch of the superior laryngeal nerve, injury, classification, operative time and voice outcomes at 2 weeks and 3 months post-intervention were noted in both the groups. Data was analysed using SPSS 22. Results: Of the 102 patients, 50(49%) were in group A; 5(10%) males and 45(90%) females with mean age 40.48±12.58 years and mean body mass index 30.676±2.305. There were 52(51%) patients in group B; 5(9.6%) males and 45(90.4%) females with mean age 39.67±11.60 years and mean body mass index 30.096±2.776. The rate of external branch of the superior laryngeal nerve identification was higher and the operative time was shorter in group B compared to group A (p=0.05). No significant difference was noted in terms of voice outcomes either at baseline or at any of the two follow-up points between the groups (p>0.05). Conclusion: The transection of sternothyroid muscle improved the rate of external branch of the superior laryngeal nerve exposure and preservation compared to the conventional technique during thyroidectomy. Keywords: Thyroidectomy, Thyroid gland, Laryngeal nerves, Acoustics, Vocal cords, Sternothyroid muscle.